Combined effects of warming and ocean acidification on coral reef Foraminifera Marginopora vertebralis and Heterostegina depressa - Schmidt, Christiane; Kucera, Michal; Uthicke, Sven (Coral reefs, 2014)
Warming and changes in ocean carbonate chemistry alter marine coastal ecosystems at an accelerating pace. The interaction between these stressors has been the subject of recent studies on reef organisms such as corals, bryozoa, molluscs, and crustose coralline algae. Here we investigated the combined effects of elevated sea surface temperatures and p CO 2 on two species of photosymbiont-bearing coral reef Foraminifera: Heterostegina depressa (hosting diatoms) and Marginopora vertebralis (hosting dinoflagellates). The effects of single and combined stressors were studied by monitoring survivorship, growth, and physiological parameters, such as respiration, photochemistry (pulse amplitude modulation fluorometry and oxygen production), and chl a content. Specimens were exposed in flow-through aquaria for up to seven weeks to combinations of two p CO 2 (~790 and ~490 µatm) and two temperature (28 and 31 °C) regimes. Elevated temperature had negative effects on the physiology of both species. Elevated p CO 2 had negative effects on growth and apparent photosynthetic rate in H.depressa but a positive effect on effective quantum yield. With increasing p CO 2 , chl a content decreased in H. depressa and increased in M. vertebralis. The strongest stress responses were observed when the two stressors acted in combination. An interaction term was statistically significant in half of the measured parameters. Further exploration revealed that 75 % of these cases showed a synergistic (= larger than additive) interaction between the two stressors. These results indicate that negative physiological effects on photosymbiont-bearing coral reef Foraminifera are likely to be stronger under simultaneous acidification and temperature rise than what would be expected from the effect of each of the stressors individually.